The trial of Thomas Paterson, for blasphemy, before the High Court of Justiciary, Edinburgh, with the whole of his bold and effective defence. Also, the trials of Thomas Finlay and Miss Matilda Roalfe (for blasphemy), in the Sheriffs' Court. With notes and a special dissertation on blasphemy prosecutions in general, by the secretary of the "Anti-persecution Union" [= G.J. Holyoake] (Anti-persecution Union, 1844)
With: "The man Paterson"